CONTEMPORARY REFLECTIONS ON THE INTERSECTIONS OF POLITICS, CORRUPTION AND SPORTS (Security Dialogues, 2025)
This paper aims to present the negative impacts of politics and corruption onsports as a social phenomenon, which, due to such malign influences, is increasingly movingaway from its original humanistic concept. The impact of politics and corruption is drivingsports towards dehumanisation and national, religious, and racial discrimination of all itsparticipants. Sports have become a battleground for power struggles between superpowersand small states, with nationalism and xenophobia imposing characteristics that contradictthe very essence of sports.Today, sports are a crucial aspect of the ideological operations of systems that use sportsto solve certain problems or as a mobilising force to support the system. Often, sports aretreated as a means of achieving the basic ideological goals of society or the government.Sports have become an ideological tool to deceive the masses and maintain the control ofthe ruling powers. The integration of politics, sports, and power allows sports to be turnedinto entertainment for the masses, and under the motto “bread and circuses,” the people areturned into an audience, a crowd, which, through repressive behaviour control, absorbs socialdiscontent arising from the marginal social position of certain groups.Sports are suitable for influencing the masses, especially the youth, and for affirming variouspolitical ideologies and social anomalies and irregularities. Therefore, corruption, a negativephenomenon that has not spared sports despite its initially noble assumptions, is not new. Inone form or another, it has always existed. Corruption appears in various forms throughoutsports, undermining honesty, fair play, and trust in the game. The increasing amounts ofmoney inherent in sports make this industry susceptible to corruption, while the participantsbecome addicted to power, elitism, and betting.
Keywords: Dehumanization, ideological goals, political ideologies, corruption, social groups